Novel Multiple-Input Single-Output Shadow Filter with Improved Passband Gain Using Multiple-Input Multiple-Output DDTAs - Montree Kumngern; Fabian Khateb; Tomasz Kulej (Electronics, 2025)
This paper presents a multiple-input single-output (MISO) shadow filter implemented using multiple-input differential difference transconductance amplifiers (MI-DDTAs). The MI-DDTA’s multiple inputs are realized through the multiple-input bulk-driven MOS transistor (MI-BD MOST) technique. Leveraging the multiple-input capability of the DDTA, various filter responses—low-pass filter (LPF), high-pass filter (HPF), band-pass filter (BPF), band-stop filter (BSF), and all-pass filter (APF)—can be efficiently achieved by appropriately configuring the input signals. The natural frequency and quality factor of the shadow filter can be independently tuned using external amplifiers. Unlike conventional shadow filters, where adjusting the quality factor or natural frequency impacts the passband gain, this design ensures a constant unity passband gain. The MI-DDTA operates at a supply voltage of 0.5 V and consumes 385.8 nW of power for setting current Iset = 14 nA. The proposed MI-DDTA and shadow filter are designed and validated through simulations in the Cadence design environment, using a 0.18 µm CMOS process provided by TSMC (Taiwan Semiconductor Manufacturing Company Limited).
Keywords: Advanced Fiber Optic Sensors; Optical Network Technologies; Photonic and Optical Devices